Understanding the adult learner: The substance for effective teaching - Orobor, M. E.; Apiti, A. A.; Ejiro-Mitaire F. O. (Journal of Research in Adult and Continuing Education, 2023)
The adult learners are those who sometimes had no access to formal education, before attaining adulthood. Adulthood in this context involves psychological, sociological, political, financial, spiritual, cognitive or intellectual, professional and biological maturities alongside with various characteristics. The educators or facilitators or instructors should understand these variables in the adult learners in order to attain effective teaching and learning. The psychological and other forms of the adult learners must be viewed against their needs, emotions; anxiety; fear; adjustment; self-esteem; self-concept; self-fulfillment; and motivation.Besides, the facilitators or instructors should also consider the following functions of the adult learners in order to make learning effective such as arousal function; expectancy function; incentive function; and, disciplinary function. There is need for the educator to be less formal in dealing with adult learners, need to promote self-confidence in the adult learner; to reduce fear; and, the need to make learning more relevant. The applications of these factors will not only make the facilitators or instructors to understand the adult learner, but it will bring about the substance of learning for effective teaching.
Keywords: Adult Learner; Teaching